Comprehensive safety assessment of a hydrogen liquefaction system based on an integrated system-theoretic process analysis (STPA) and best-worst method (BWM) - Wang, Jingjing; Qi, Meng; Liu, Shangzhi; Zhao, Dongfeng (International journal of hydrogen energy, 2024)
Hydrogen energy stands at the forefront of low carbon energy development owing to its environmentally friendly attributes. The storage and transportation of hydrogen have emerged as pivotal components in constructing the hydrogen value chain. Although liquid hydrogen represents a primary method for storing and transporting hydrogen across remote areas, the liquefaction process entails significant energy conversion and harsh operating conditions. In addition, hydrogen is characterized by its wide flammability limit, low minimum ignition energy, and susceptibility to hydrogen embrittlement with metals, leading to high leakage probabilities. These factors raise safety concerns for hydrogen liquefaction. However, the system safety of the hydrogen liquefaction system remains a notable gap in hydrogen safety research. In this study, we apply system-theoretic process analysis (STPA) to identify system hazards and improve the STPA by integrating a best-worst method (BWM) to quantify the risk of hazards in the hydrogen liquefaction system. The STPA-BWM method effectively ranks identified hazards, showing that hydrogen leakage due to equipment damage is the most severe hazard in the hydrogen liquefaction system. This is followed by system pressures above normal due to leaks and rupture of equipment and pipelines. As a result, 14 control actions (CAs) and 24 unsafe control actions (UCAs) are identified. Possible causal factors for UCAs are analyzed, and corresponding low-level safety constraints are proposed. The qualitative and quantitative hazard assessment of hydrogen liquefaction systems can provide a basis for enhancing the safety and reliability of such systems. •Proposing an integrated STPA-BWM for risk analysis.•Assessing risks in hydrogen liquefaction system using the proposed methodology.•Developing a risk control strategy for hydrogen liquefaction system.